2003
DOI: 10.1051/animres:2003005
|View full text |Cite
|
Sign up to set email alerts
|

Growth, carcass composition and meat quality response to dietary concentrations in fast-, medium- and slow-growing commercial broilers

Abstract: -Growth, carcass composition and certain meat quality traits were studied in fast (F), medium (M) and slow (S) growing broilers fed with 3 regimes appropriate for each chicken type and differing on average by 418 kJ·kg -1 AMEn and 1% crude protein (P1 > P2 > P3). No significant interactions between chicken types and feed were measured before 3 weeks and after 6 weeks of age, indicating that the 3 genotypes had similar responses to the 3 diets during these periods. Before 3 weeks of age, body weight was 5% high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
33
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 18 publications
17
33
0
6
Order By: Relevance
“…These conditions possibly influenced the uniformity of the pH values found among the treatments in the present study. Literature reports results that are consistent with the findings of the present study (Lonergan et al, 2003;Quentin et al, 2003 andSantos et al, 2005).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These conditions possibly influenced the uniformity of the pH values found among the treatments in the present study. Literature reports results that are consistent with the findings of the present study (Lonergan et al, 2003;Quentin et al, 2003 andSantos et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…Genetic factors possibly have higher influence on color parameters than pH in Paraíso Pedrês meat. The effect of genotype on color parameters was reported by several authors, including Berri et al (2005), Castellini et al (2002b), Grashorn & Clostermann (2002), and Quentin et al (2003). When tissues (breast and thighs) were compared as to redness (a*), it was found that Cobb ® birds presented higher a* values in the breast as compared to the free-range strains (Table 2).…”
mentioning
confidence: 60%
“…Thus, the most appreciate parts are breast and drumstick, and their percentages over total carcass are good markers of the animal economic value. The value of 15.07% for breast found in Mos roosters remained in the same order than values found by Quentin et al (2003) for a commercial French 'label' type and by Berry et al (2001) for a genetically selected broiler strain. Similar results were observed by Jaturashita et al (2008), for an indigenous Thai breed, who reported values around 15.5% for breast yield.…”
Section: Discussionsupporting
confidence: 67%
“…It was reported that meat type birds performed better with increasing amino acids densities (Zhai et al 2013(Zhai et al , 2014. Panda et al (2011) fed broiler 1.3% Lys with a specific ratio to other amino acid and, observed better results, indicating that concentrated diets can improve F:G in broiler (Quentin et al 2003). Moreover, improved F:G in high and medium Lys groups may be attributed to the higher WG and lower FI in the same groups.…”
Section: Resultsmentioning
confidence: 89%
“…Dietary Lys is important for maintenance and skeletal muscle accretion (Dozier et al 2007;Ayasan & Okan, 2010). Supplementation of Lys during early growth stages (Ayasan & Okan, 2006;Campestrini et al 2010) is beneficial because it involves the regulation of the protein synthesis and increases muscle growth (Eits et al 2003), improve weight gain and feed efficiency (Quentin et al 2003;Si et al 2004). Chickens grow faster at a relatively high dietary Lys concentration in the diet compared with diet deficient in Lys (Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%